Flexible photochromic Ag:TiO2 thin films fabricated by ink-jet and flexography printing processes. Issue 103 (6th October 2015) - Tricot, F.; Vocanson, F.; Chaussy, D.; Beneventi, D.; Party, M.; Destouches, N.
Abstract : Printing techniques compatible with industrial production are successfully used to fabricate photochromic Ag:TiO2 thin films on a plastic substrate. Abstract : The realization of a flexible Ag:TiO2 photochromic material using processes compatible with industrial scale production is demonstrated. A titanium precursor solution is printed on a plastic substrate. After incorporating silver, the coating shows a reversible photochromic behavior with a good contrast of color under laser exposures.